2016
DOI: 10.1038/ng.3502
|View full text |Cite
|
Sign up to set email alerts
|

An oncogenic MYB feedback loop drives alternate cell fates in adenoid cystic carcinoma

Abstract: Translocation events are frequent in cancer and may create chimeric fusions or ‘regulatory rearrangements’ that drive oncogene overexpression. Here we identify super-enhancer translocations that drive overexpression of the oncogenic transcription factor MYB as a recurrent theme in adenoid cystic carcinoma (ACC). Whole-genome sequencing data and chromatin maps reveal distinct chromosomal rearrangements that juxtapose super-enhancers to the MYB locus. Chromosome conformation capture confirms that the translocate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
239
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 245 publications
(248 citation statements)
references
References 54 publications
8
239
1
Order By: Relevance
“…Moreover, RAD51C is a MYB-regulated gene (Quintana et al, 2011, Drier et al, 2016. My data in Figures 4.9 and 4.10 show that silencing MYB in the MYB shRNA cells did not detectably change the total amount of RAD51 or cytosolic RAD51 expression, but reduced nuclear RAD51 expression after exposure to +Dox+ETO treatment.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…Moreover, RAD51C is a MYB-regulated gene (Quintana et al, 2011, Drier et al, 2016. My data in Figures 4.9 and 4.10 show that silencing MYB in the MYB shRNA cells did not detectably change the total amount of RAD51 or cytosolic RAD51 expression, but reduced nuclear RAD51 expression after exposure to +Dox+ETO treatment.…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies indicated that several genes (BRCA1, CEP164 and TOPBP1) that were involved in DNA repair were MYB target genes (Quintana et al, 2011, Drier et al, 2016. Furthermore, both BRCA1 (Cousineau et al, 2005) and TOPBP1 (Moudry et al, 2016) regulate RAD51 function in response to DNA damage.…”
Section: 27)mentioning
confidence: 99%
See 3 more Smart Citations